Cultural Differences in Work-Life Balance (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article delves into the cultural differences in work-life balance across Western and Eastern countries, as well as Uzbekistan, examining how cultural values, social norms, and economic conditions shape people's approach to balancing work and personal life. In Western countries like the New Zealand and those in Western Europe, there is a strong focus on personal freedom, efficiency, and structured work hours, with an increasing shift towards flexible work options and mental well-being. On the other hand, Eastern countries such as Japan, China, and India often emphasize dedication and long working hours, though there is a growing awareness of the need for rest and balance. Uzbekistan offers a distinctive perspective, combining deep-rooted traditions with evolving modern work practices. Family and community play a central role in shaping work-life balance, while economic progress continues to influence workplace dynamics. Recognizing these cultural differences is crucial for building inclusive, supportive work environments and encouraging global organizational growth.